2020
DOI: 10.3390/su12104153
|View full text |Cite
|
Sign up to set email alerts
|

How Audit Quality Affects the Firm Performance with the Moderating Role of the Product Market Competition: Empirical Evidence from Pakistani Manufacturing Firms

Abstract: Audit quality (AQ) is a crucial instrument for ensuring transparency and accountability in both the public and private sectors. If the AQ is responsible for the maximization or minimization of profit, then what are the circumstances that make these possible? In this study, we examined the role of the product market competition (PMC) in the relation between the AQ and firm performance (FP). The PMC on the manufacturing firms of Pakistan was divided into two categories—low product market competition (LPMC) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 77 publications
0
23
0
1
Order By: Relevance
“…Fourthly, the findings of this study reported that AQ and firm performance have a positive connection. In this context, Sattar, Javeed and Latief [44] discovered that the quality of audit is highly beneficial for firm performance in Pakistan. Bonazzi and Islam [140] discovered that agency cost can be minimized by appointing a quality auditor, which highlights every financial and non-financial aspect of a firm clearly and truly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourthly, the findings of this study reported that AQ and firm performance have a positive connection. In this context, Sattar, Javeed and Latief [44] discovered that the quality of audit is highly beneficial for firm performance in Pakistan. Bonazzi and Islam [140] discovered that agency cost can be minimized by appointing a quality auditor, which highlights every financial and non-financial aspect of a firm clearly and truly.…”
Section: Discussionmentioning
confidence: 99%
“…They established that audit quality is helpful to improve firm performance. Besides, Al Ani, et al [ 43 ] and Sattar, et al [ 44 ] also supported the role of auditing practices for the improvement of firm performance. By following theoretical and empirical analysis, this study has developed various hypotheses:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
“…Recently, transparent sustainability reporting is becoming a prime responsibility of business organisations, compelling the ACs to supervise the sustainability reporting to promote stockholder confidence. The Cadbury code suggests forming an AC to follow the rules and regulations and examine the financial records to avoid misstatements or fraud (Sattar et al , 2020). Hąbek and Wolniak (2016) studied the quality of audit reports in a sample of six European countries and indicated the low quality of the sustainability reports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The AC oversees the work of the internal auditors who work in association with the external auditor to complete the reporting process in a firm (Eluyela et al , 2018; Saibaba and Ansari, 2011). Similarly, the AC role has also been researched from various aspects to produce better quality non-financial statements (Sattar et al , 2020). Similarly, Appuhami and Tashakor (2017) examined the role of AC characteristics on the CSR disclosure of Australian firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The discretionary methods for measuring the quality of revenues were chosen as a proxy method in our study due to the fact that they capture the slight variations in audit quality that are relevant in terms of taking measures to readjust the significance threshold and in allowing or justifying the sample's fairly limited number. As suggested by the studied specialty literature, the number of clients [70], the size of the audit company [71] and the company's achievements and growth [72] have a significant impact on the audit quality itself. However, so far studies are limited in terms of the evaluation of the impact of financial crises on audit quality [73].…”
Section: Resultsmentioning
confidence: 99%